(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The article substantiates the relevance of the study of history in the context of the unity of the concepts of past-present-future. At the same time, these concepts of measuring historical time are considered in the process of interconnection with the concept of continuity.